A tissue engineered model of the intestinal lacteal for evaluating lipid transport by lymphatics - Dixon, J. Brandon (2009)
Lacteals are the entry point of all dietary lipids into the circulation, yet little is known about the active regulation of lipid uptake by these lymphatic vessels, and there lacks in vitro models to study the lacteal – enterocyte interface. We describe an in vitro model of the human intestinal microenvironment containing differentiated Caco-2 cells and lymphatic endothelial cells (LECs). We characterize the model for fatty acid, lipoprotein, albumin, and dextran transport, and compare to qualitative uptake of fatty acids into lacteals in vivo. We demonstrate relevant morphological features of both cell types and strongly polarized transport of fatty acid in the intestinal-to-lymphatic direction. We found much higher transport rates of lipid than of dextran or albumin across the lymphatic endothelial monolayer, suggesting most lipid transport is active and intracellular. This was confirmed with confocal imaging of Bodipy, a fluorescent fatty acid, along with transmission electron microscopy. Since our model recapitulates crucial aspects of the in vivo lymphatic-enterocyte interface, it is useful for studying the biology of lipid transport by lymphatics and as a tool for screening drugs and nanoparticles that target intestinal lymphatics.